2011
DOI: 10.1002/chem.201102722
|View full text |Cite
|
Sign up to set email alerts
|

Installation of Amine Moieties into a Polycyclic Anodic Product Derived from 2,4‐Dimethylphenol

Abstract: When 2,4-dimethylphenol is anodically treated, a dehydrotetramer with four contiguous stereocentres is readily obtained on a multi-gram scale. The substitution of a 2,4-dimethyl-phenoxy fragment by several amines was demonstrated, and the best results were obtained with primary amines. Optically pure α-chiral aliphatic amines yield diastereomeric mixtures that can be separated in most cases. The basic amine causes a partial hemiketal-opening of the bisbenzofuran moiety leading to an equilibrium within an α,β-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…The reaction conditions were chosen on the basis of previous publications . Boron-doped diamond (BDD) as the anode material has proven its outstanding performance in anodic C–C coupling in many cases. , Additionally, the use of HFIP as the solvent is mandatory in electro-organic coupling reactions, as it is considered essential for obtaining the desired reaction selectivity. , By hydrogen bonding, the oxygen functionality is blocked, avoiding the typical C–O bond formation and/or the generation of polycyclic molecular architectures. ,− …”
Section: Resultsmentioning
confidence: 99%
“…The reaction conditions were chosen on the basis of previous publications . Boron-doped diamond (BDD) as the anode material has proven its outstanding performance in anodic C–C coupling in many cases. , Additionally, the use of HFIP as the solvent is mandatory in electro-organic coupling reactions, as it is considered essential for obtaining the desired reaction selectivity. , By hydrogen bonding, the oxygen functionality is blocked, avoiding the typical C–O bond formation and/or the generation of polycyclic molecular architectures. ,− …”
Section: Resultsmentioning
confidence: 99%
“…Treatment with NH 4 F or amines in the presence of a CsF promotor yielded amino-functionalized Pummerer ketones (e.g., 183.5 and 183.6 ). 511 Treatment with anisole in the presence of BF 3 ·OEt 2 gave Friedel–Crafts product 183.7 , a scaffold which is remarkably similar to naturally occurring rocaglamide—an antileukemic flavagline. 512 Finally, treatment with ketones or isocyanates in the presence of BF 3 ·OEt 2 led to [3+2] cycloaddition products (e.g., 183.8 ).…”
Section: O -Centered Radical Generation From O–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 97%
“…The electron‐rich properties associated with phenolic compounds make them particularly amenable to oxidation, a feature that makes them especially attractive in natural product synthesis . Early studies by the Waldvogel laboratory have demonstrated that phenols can be electro‐oxidatively coupled to produce biphenols as well as polycyclic scaffolds . A related strategy was recently employed by the Opatz and Waldvogel groups in the syntheses of (−)‐thebaine and (−)‐oxycodone .…”
Section: Anodic Oxidationmentioning
confidence: 99%